Two-chair dialogue: an emotion-focused technique applied to career counselling - Cardoso, Paulo (2020)
This article aims to show the applicability of two-chair dialogue techniques to solve intrapersonal conflicts underpinning career decision-making difficulties. Grounded in a dialectical constructivist perspective this technique evokes the dialogue between two conflicting self-position, each one in a different chair. It is sought that this dialogue fosters harmony between both sides of the conflict to facilitate career decisionmaking. An illustrative case is presented to describe the sequence of counsellor’s tasks during the process of facilitating conflict resolution. Next, critical aspects of the intervention are commented, namely the role of emotions and working alliance to foster client change. Finally, we refer to the advantages of this technique for flexible and dynamic practices, committed to abolishing frontiers between career and personal counselling.